Testosterone enhances expression and functional activity of epithelial sodium channel (ENaC), cystic fibrosis transmembrane regulator (CFTR) and sodium hydrogen exchanger (NHE) in vas deferens of sex-steroid deficient male rats - Ramli, Nur Siti Khadijah; Giribabu, Nelli; Salleh, Naguib (Elsevier, 2018)
Effects of testosterone on expression and functional activity of ENaC, CFTR and NHE in vas deferens were investigated. Methods: Orchidectomized, adult male rats were given 125 and 250 μg/kg/day testosterone subcutaneously, with or without flutamide and finasteride for seven consecutive days. At the end of the treatment, rats were anesthetized and vas deferens were perfused. Changes in vas deferens fluid secretion rate, pH, HCO 3 − , Cl − and Na + concentrations were recorded in the presence of amiloride and Cftr inh-172. Rats were then sacrificed and vas deferens were harvested and subjected for molecular biological analysis. Results: Testosterone treatment caused the fluid pH and HCO 3 − concentrations to decrease but secretion rate, Cl − and Na + concentrations to increase, where upon amiloride administration, the pH and HCO 3 − concentration increased but Cl − and Na + concentrations further increased. In testosterone-treated rats, administration of Cftr inh-172 caused all fluid parameters to decrease. In testosterone-treated rats co-administered with flutamide or finasteride, pH and HCO 3 − concentration increased but fluid secretion rate, Cl − and Na + concentrations decreased and these parameters were not affected by amiloride or Cftr inh-172 administration. Under testosterone influence, CFTR and γ-ENaC were highly expressed at the apical membrane while NHE-1 and 4 were highly expressed at the basolateral membrane of vas deferens epithelium. Meanwhile, NHE-2 and 3 were highly expressed at the apical membrane. Conclusions: Differential expression of ENaC, CFTR and NHE in vas deferens under testosterone influence indicated the important role of these transporters in creating optimal fluid microenvironment that is essential for preserving male fertility.